Experience-Dependent Effects of Muscimol-Induced Hippocampal Excitation on Mnemonic Discrimination - Johnson, Sarah A.; Turner, Sean M.; Lubke, Katelyn N.; Cooper, Tara L.; Fertal, Kaeli E.; Bizon, Jennifer L.; Maurer, Andrew P.; Burke, Sara N. (Frontiers in Systems Neuroscience, 2019)
Memory requires similar episodes with overlapping features to be represented distinctly, a process that is disrupted in many clinical conditions as well as normal aging. Data from humans have linked this ability to activity in hippocampal CA3 and dentate gyrus (DG). While animal models have shown the perirhinal cortex is critical for disambiguating similar stimuli, hippocampal activity has not been causally linked to discrimination abilities. The goal of the current study was to determine how disrupting CA3/DG activity would impact performance on a rodent mnemonic discrimination task. Rats were surgically implanted with bilateral guide cannulae targeting dorsal CA3/DG. In Exp.1, the effect of intra-hippocampal muscimol on target-lure discrimination was assessed within subjects in randomized blocks. Muscimol initially impaired discrimination across all levels of target-lure similarity, but performance improved on subsequent test blocks irrespective of stimulus similarity and infusion condition. To clarify these results, Exp.2 examined whether prior experience with objects influenced the effect of muscimol on target-lure discrimination. Rats that received vehicle infusions in a first test block, followed by muscimol in a second block, did not show discrimination impairments for target-lure pairs of any similarity. In contrast, rats that received muscimol infusions in the first test block were impaired across all levels of target-lure similarity. Following discrimination tests, rats from Exp.2 were trained on a spatial alternation task. Muscimol infusions increased the number of spatial errors made, relative to vehicle infusions, confirming that muscimol remained effective in disrupting behavioral performance. At the conclusion of behavioral experiments, fluorescence in situ hybridization for the immediate-early genes Arc and Homer1a was used to determine the proportion of neurons active following muscimol infusion. Contrary to expectations, muscimol increased neural activity in DG. An additional experiment was carried out to quantify neural activity in naïve rats that received an intra-hippocampal infusion of vehicle or muscimol. Results confirmed that muscimol led to DG excitation, likely through its actions on interneuron populations in hilar and molecular layers of DG and consequent disinhibition of principal cells. Taken together, our results suggest disruption of coordinated neural activity across the hippocampus impairs mnemonic discrimination when lure stimuli are novel.